Factors relating to high psychological distress in Indigenous Australians and their contribution to Indigenous–non‐Indigenous disparities. (31st January 2018) - McNamara, Bridgette J.; Banks, Emily; Gubhaju, Lina; Joshy, Grace; Williamson, Anna; Raphael, Beverley; Eades, Sandra
Abstract: Objective: To explore factors associated with high psychological distress among Aboriginal and non‐Aboriginal Australians and their contribution to the elevated distress prevalence among Aboriginal people. Methods: Questionnaire data from 1, 631 Aboriginal and 233, 405 non‐Aboriginal 45 and Up Study (NSW, Australia) participants aged ≥45 years were used to calculate adjusted prevalence ratios for high psychological distress (Kessler‐10 score ≥22) for socio‐demographic, health and disability‐related factors, and to quantify contributions to differences in distress prevalence. Results: While high‐distress prevalence was increased around three‐fold in Aboriginal versus non‐Aboriginal participants, distress‐related risk factors were similar. Morbidity and physical disability had the strongest associations; high distress affected 43.8% of Aboriginal and 20.9% of non‐Aboriginal participants with severe physical limitations and 9.5% and 3.9% of those without limitations, respectively. Differences in distress prevalence between Aboriginal and non‐Aboriginal participants were essentially attributable to differences in SES, morbidity, disability/functional limitations and social support (fully‐adjusted PR 1.19 [95% 1.08, 1.30]); physical morbidity and disability explained the bulk. Conclusions: The markedly elevated prevalence of high distress among older Aboriginal Australians appears largely attributable to greater physical morbidity and disability. Implications for public health: Addressing upstream determinants of physical morbidity and improved integration of social and emotional wellbeing care into primary care and chronic disease management are essential.